A Study on Professional Commitment of Government School Teachers of East District of Sikkim - Bhowmik, Arup; Sharma, Bed Prasad (JOURNAL OF INDIAN EDUCATION, 2020)
Total commitment toward the teaching profession is a common denominator among all successful and ideal teachers; total commitment is total involvement, much more than merely working hard. The present study aimed to investigate the level of professional commitment of school teachers in the East district of Sikkim with regards to their gender, locality of the school, level of teaching, academic and professional qualifications, and teaching experience. The study found a moderate level of professional commitment among the teachers. Further, no significant variations in professional commitment were found based on gender, locality, duration of teaching experience, professional qualification, level of teaching, and different factors of professional commitment. However, a significant difference was found among teachers based on their academic qualifications.